Functionalized Mesoporous Silicon Nanomaterials in Inorganic Soil Pollution Research: Opportunities for Soil Protection and Advanced Chemical Imaging - Yang, Jia-Wei; Fang, Wen; Williams, Paul N.; McGrath, John W.; Eismann, Carlos Eduardo [UNESP]; Menegário, Amauri Antonio [UNESP]; Elias, Lucas Pellegrini [UNESP]; Luo, Jun; Xu, Yingjian (Springer Nature, 2020)
“Innovative actions towards a pollution free-planet” is a goal of the United Nations Environment Assembly (UNEA). Aided by both the Food and Agricultural Organisation (FAO) and its Global Soil Partnership under the 3rd UNEA resolution, a consensus from > 170 countries have agreed a need for accelerated action and collaboration to combat soil pollution. This initiative has been tasked to find new and improved solutions to prevent and reduce soil pollution, and it is in this context that this review provides an updated perspective on an emerging technology platform that has already provided demonstrable utility for measurement, mapping, and monitoring of toxic trace elements (TTEs) in soils, in addition to the entrapment, removal, and remediation of pollutant sources. In this article, the development and characteristics of functionalized mesoporous silica nanomaterials (FMSN) will be discussed and compared with other common metal scavenging materials. The chemistries of the common functionalizations will be reviewed, in addition to providing an outlook on some of the future directions/applications of FMSN. The use of FMSN in soil will be considered with some specific case studies focusing on Hg and As. Finally, the advantages and developments of FMSN in the widely used diffusive gradients-in-thin films (DGT) technique will be discussed, in particular, its advantages as a DGT substrate for integration with oxygen planar optodes in multilayer systems that provide 2D mapping of metal pollutant fluxes at submillimeter resolution, which can be used to measure detailed sediment-water fluxes as well as soil-root interactions, to predict plant uptake and bioavailability.
Keywords: Diffusive gradient in thin films (DGT); Functional mesoporous silicon nanomaterials (FMSN); Heavy metals; Soil pollution; X-ray fluorescence spectrometry (XRF)